The Problems with Crisis Pregnancy Centers: Reviewing the Literature and Identifying New Directions for Future Research - Montoya MN; Judge-Golden C; Swartz JJ (Dove Medical Press, 2022)
Melissa N Montoya, Colleen Judge-Golden, Jonas J Swartz Department of Obstetrics & Gynecology, Duke University School of Medicine, Durham, NC, USACorrespondence: Jonas J Swartz, Department of Obstetrics & Gynecology, Duke University, DUMC, 3084, Durham, NC, 27710, USA, Tel +1 919 668 7594, Fax +1 919 681 0739, Email jonas.swartz@duke.eduAbstract: Crisis pregnancy centers (CPCs) are nonprofit organizations that present themselves as healthcare clinics while providing counseling explicitly intended to discourage and limit access to abortion. These facilities engage in purposefully manipulative and deceptive practices that spread misinformation on sexual health and abortion. CPCs have also been shown to delay access to medically legitimate prenatal and abortion care, which negatively impacts maternal health. Along with increasing anti-abortion legislation, the proliferation of CPCs paired with the closure of abortion clinics exacerbates the ongoing harmful impact these centers have on the reproductive healthcare landscape; however, despite their growing influence, there is still limited research on patients' understanding of and experiences with CPCs. This article provides a review of academic literature on CPCs and suggests future directions for research. Ongoing scholarship may aid in improving patient awareness and education regarding CPCs, an important step toward protecting reproductive autonomy.Keywords: reproductive health, reproductive justice, abortion, advocacy